Makeup as a Form of Self-Representation: Queer Beauty Vlogger: Makeup sebagai Bentuk Representasi Diri: Queer Beauty Vlogger - Devi Loveitha; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative research explores makeup as a form of self-representation by queer beauty vlogger Deta Cahyaa. Applying Roland Barthes' semiotic theory, the study focuses on denotation, connotation, and myth concepts. Utilizing additional insights from Stuart Hall's Representation theory, the research employs an intensional approach to understand the nuances of makeup representation by queer beauty vlogger Deta Cahyaa in his YouTube channel. Through observational and documentary methods, the analysis reveals that queer representation in makeup has evolved beyond societal myths, transforming into a professional representation rather than reinforcing traditional stereotypes. The findings, illustrated through videos titled